Were they really brawls? Polish interventions in Moldavia in the years 1595–1616 - Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 2021)
This paper was written in connection with the thesis that Polish interventions in Moldavia conducted in the years 1595–1616 were a result of the private policy of first Jan Zamoyski, and later the magnates – sons-in-law of Jeremy Movila. By analyzing the political and legal situation of the hospodars of Moldavia from the Movila dynasty towards the Polish king , I try to prove that all interventions were either completely or unofficially connected with the state policy of the Republic of Poland. The last intervention in the years 1615–1616 was the most controversial one, but the lack of support for it was not due to political reasons, but to personal ones.